Evaluasi Kebutuhan Lahan Parkir Pasar Hewan Ketapang Kabupaten Sampang - Royzikin, Ahmad; Pandulu, Galih Damar; Primasworo, Rifky Aldila (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Ketapang Animal Market is one of the animal markets in Sampang Regency, which causes many people in the area and outside the area to carry out animal buying and selling transactions which results in an increase in the number of visitor vehicles going in and out of the market area at a certain time so that the available parking locations exceed capacity. Parking conditions in the market area are also irregular, indicated by violations, for example 2-wheeled or 4-wheeled vehicles parked on the shoulder of the road do not comply with the rules. Therefore, this analysis was carried out to meet the needs of parking areas in the market area. To find out, this is done by analyzing parking characteristics, the area of ​​parking requirements and side obstacles around the road to find out how high the value of side obstacles is on the shoulder of the road. The discussion results from this research show a high parking turnover rate, namely 6 vehicles/SRP, and a parking index >1, which means the capacity is smaller than required. The evaluation results are based on alternative angles, the 90° angle corresponds to an area of ​​830 m2 for two wheels and 4,015 m2 for four wheels. Side obstacles are categorized as High/T class with a value of 566.3/hour 777.425/hour, but after evaluating the frequency of occurrence The value obtained for side resistance is 457.55/hour, which is included in the medium class.